2017
DOI: 10.3413/nukmed-0851-16-10
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of 99mTc-HYNICTOC SPECT/CT over whole-body planar scintigraphy and SPECT in patients with neuroendocrine tumours

Abstract: The sensitivity and diagnostic accuracy of SPECT/CT in the evaluation of NET lesions outperforms planar WB imaging or SPECT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Some studies have compared MIBI to FDG PET/CT in multiple myeloma [ 10 , 11 ]; however, in our knowledge, none of them systematically included single-photon emission computed tomography (SPECT)/CT images for this comparation. It has been demonstrated that SPECT/CT increases the sensitivity and specificity of many scintigraphic studies [ 12 16 ]. It provides precise localization and characterization of abnormal foci, reducing false positives due to physiologic uptake, influencing the staging and clinical management as well as reader confidence [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have compared MIBI to FDG PET/CT in multiple myeloma [ 10 , 11 ]; however, in our knowledge, none of them systematically included single-photon emission computed tomography (SPECT)/CT images for this comparation. It has been demonstrated that SPECT/CT increases the sensitivity and specificity of many scintigraphic studies [ 12 16 ]. It provides precise localization and characterization of abnormal foci, reducing false positives due to physiologic uptake, influencing the staging and clinical management as well as reader confidence [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that SPECT/CT increases the sensitivity and specificity of many scintigraphic studies [ 12 16 ]. It provides precise localization and characterization of abnormal foci, reducing false positives due to physiologic uptake, influencing the staging and clinical management as well as reader confidence [ 12 16 ]. The aim of this study was to compare MIBI SPECT/CT with FDG PET/CT at multiple myeloma staging.…”
Section: Introductionmentioning
confidence: 99%